An Experimental Analysis of Three Pseudo-peripheral Vertex Finders in conjunction with the Reverse Cuthill-McKee Method for Bandwidth Reduction - GONZAGA DE OLIVEIRA,S. L. (2019)
Abstract. The need to determine pseudoperipheral vertices arises from several graph-theoretical approaches for ordering sparse matrix equations. The results of two algorithms for finding such vertices, namely, the George-Liu and Kaveh-Bondarabady algorithms, are evaluated in this work along with a variant of the Kaveh-Bondarabady algorithm. The results suggest that the well-know George-Liu algorithm dominates the other two pseudoperipheral vertex finders mainly when considering the computational times of the algorithms.